Evaluation of (−)-epicatechin metabolites as recovery biomarker of dietary flavan-3-ol intake - Javier I. Ottaviani (Nature Portfolio, 2019)
Abstract Data from dietary intervention studies suggest that intake of (−)-epicatechin mediates beneficial vascular effects in humans. However, population-based investigations are required to evaluate associations between habitual intake and health and these studies rely on accurate estimates of intake, which nutritional biomarkers can provide. Here, we evaluate a series of structurally related (−)-epicatechin metabolites (SREM), particularly (−)-epicatechin-3′-glucuronide, (−)-epicatechin-3′-sulfate and 3′-O-methyl-(−)-epicatechin-5-sulfate (SREMB), as flavan-3-ol and (−)-epicatechin intake. SREMB in urine proved to be a specific indicator of (−)-epicatechin intake, showing also a strong correlation with the amount of (−)-epicatechin ingested (R2: 0.86 (95% CI 0.8l; 0.92). The median recovery of (−)-epicatechin as SREMB in 24 h urine was 10% (IQR 7–13%) and we found SREMB in the majority of participants of EPIC Norfolk (83% of 24,341) with a mean concentration of 2.4 ± 3.2 µmol/L. Our results show that SREMB are suitable as biomarker of (−)-epicatechin intake. According to evaluation criteria from IARC and the Institute of Medicine, the results obtained support use of SREMB as a recovery biomarker to estimate actual intake of (−)-epicatechin.